Uncertainty, Subjectivity, and the Economic Analysis of Law - Rizzo, Mario J. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2013)
The author tries to demonstrate the legal inconsistencies and economic difficulties involved in the claim for common law as the most efficient system. Points out conceptual confusions and internal inconsistencies in the idea of efficiency and lists some of the economic difficulties brought about by this pretense claim when admitted in the sphere of economic imbalance. Along the way, warns to some common pitfalls in a critical and constructive manner to the study of Law and Economics.